Influence of hole transport material ionization energy on the performance of perovskite solar cells. Issue 3 (12th December 2018) - Dänekamp, Benedikt; Droseros, Nikolaos; Tsokkou, Demetra; Brehm, Verena; Boix, Pablo P.; Sessolo, Michele; Banerji, Natalie; Bolink, Henk J.
Abstract : Here we show that the V oc in perovskite solar cells primarily depends on direct and trap-mediated recombination, rather than on the energetic offset between the valence band of the perovskite and the highest occupied molecular orbital of the organic transport layers. Abstract : Halide perovskites have shown excellent photophysical properties for solar cell applications which led to a rapid increase in device efficiency. Understanding the charge carrier dynamics within an active perovskite absorber and at its interfaces will be the key to further progress in their development. Here we present a series of fully evaporated devices employing hole transport materials with different ionization energies. The open circuit voltage of the devices, along with their ideality factors, confirms that the former is mainly determined by the bulk and surface recombination in the perovskite, rather than by the energetic offset between the valence band of the perovskite and the highest occupied molecular orbital of the organic transport layers. These results help to further understand the origin of the open circuit potential in perovskite solar cells, which is an important parameter that needs to be improved to further boost power conversion efficiencies.